Scintillation properties of multilayered composite scintillators based on the YAG:Ce and TbAG:Ce single crystalline films and GAGG:Ce crystal substrates - Y. Syrotych; V. Gorbenko; S. Witkiewicz-Łukaszek; T. Zorenko; M. Kaczmarek; J. Pejchal; J.A. Mares; R. Kucerkova; M. Nikl; K. Kamada; A. Yoshikawa; Yu Zorenko (Optical Materials: X)
This work demonstrates current progress of our group in developing of two- and three-layered composite for radiation monitoring of various components of mixed ionization radiation fluxes based on the epitaxial structures of Ce3+ doped garnet compounds using the Liquid Phase Epitaxy growth technique. These scintillators contain one or two single crystalline films, dedicated for registration of low-penetrating particles, and bulk single crystal substrates used for detection of high-penetrating γ-rays. For creation of two- and three-layered epitaxial structures, the single crystalline films of Ce3+ doped Y3Al5O12, Tb3Al5O12 and Tb2GdAl5O12 garnets were used. The single crystal of mixed Gd3GaxAl5-xO12:Ce garnet with fixed Ga concentrations of x = 2.3 and 3.0 are utilized as substrates. To assess the scintillation properties of these epitaxial structures, the pulse height spectra, light yield and scintillation decay kinetics were measured under excitation by α–particles (239Pu), β-particles (90Sr + 90Y) and γ–rays (137Cs). Finally, the figure-of merit of composite scintillators under study were calculated for selection of the best epitaxial structures for simultaneous registration α– and β-particles and γ–rays.